Mid-infrared optical parametric oscillation spanning 3.4–8.2 μm in a MgF2 microresonator. (21st May 2022) - Sun, Qibing; Wu, Wei; Wang, Yi; Yang, Yu; Shi, Lei; Ming, Xianshun; Wang, Leiran; Wang, Keyi; Zhao, Wei; Zhang, Wenfu
Abstract: Mid-infrared optical parametric oscillators (OPOs) offer a compelling route for accessing the 'molecular fingerprint' region and, thus, can find intensive applications such as precision spectroscopy and trace gas detection. Yet it still remains rather a challenge to realize broadband mid-infrared OPOs within a single cavity, usually limited by strict phase-matching conditions for wide spectral coverage and available pump power for adequate frequency generation. Here, we report the mid-infrared parametric oscillation spanning from 3.4 to 8.2 μ m, based on four-wave mixing in a high- Q MgF2 microresonator with optimized dispersion. The center wavelength at 4.78 μ m is determined by the continuous tunable quantum cascade laser source, which contributes to effective expansion towards longer wavelength, as well as systemic miniaturization with smaller pump module. Such results could not only shed light on new ultimates of crystal and other microresonators, but also inspire explorations on their growing potentials in near future.